Role of metformin in the management of polycystic ovary syndrome - Lashen, Hany (SAGE Publications, 2010)
Polycystic ovary syndrome is the most common endocrinological disorder affecting 4–12% of women and also the most controversial. Metformin was logically introduced to establish the extent to which hyperinsulinaemia influences the pathogenesis of the condition. Early studies were very encouraging. Randomized controlled studies and several metaanalyses have changed the picture and put the drug that was once heralded as magic in a much contracted place. More work is needed to establish its right place in particular with regards to the prevention of many gestational and long-term complications.